Pengaruh Sosialisasi Perpajakan, Sanksi Perpajakan dan Pengetahuan Perpajakan Terhadap Kepatuhan Wajib Pajak UMKM Kota Semarang - Noval Setyawan; Ratna Herawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the influence of tax socialization, tax sanctions, and tax knowledge on taxpayer compliance of MSMEs in Semarang City. The object of this study is MSME taxpayers in Semarang City. This study is a quantitative study. The determination of the research sample used a purposive sampling method and obtained a sample of 100 MSME taxpayers in Semarang City registered with the Cooperatives and MSMEs Office of Central Java Province. The data analysis method used multiple linear regression analysis. The results of the study indicate that partially and simultaneously the variables of tax socialization, tax sanctions, and tax knowledge have a positive and significant effect on taxpayer compliance.